Impressivenes in the Works of Nazar Eshonkul (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article contains impressiveness, psychologism in the works of Nazar Eshonkul , One of the most impressive aspects of Nazar Eshonkul's work is his ability to delve deep into the human psyche and explore the intricacies of human behavior. His works often focus on the internal struggles of his characters, and he uses his writing to examine the complex emotions and motivations that drive them.